Evaluation of platelet-rich plasma alone or in combination with demineralized freeze dried bone allograft in treatment of periodontal infrabony defects: A comparative clinical trial - Prerna Agarwal; Anirban Chatterjee; Shankar Gokhale; Himanshu Pratap Singh; Abhishek Kandwal (Wolters Kluwer Medknow Publications, 2016)
Aims: The use of platelet-rich plasma (PRP) alone in periodontal defects has been controversial and inconclusive. Hence, the present study was designed with the aim to assess the clinical and radiographic effectiveness of PRP alone in infrabony defects. Materials and Methods: Thirty infrabony defects were treated with either autologous PRP with open flap debridement (OFD) or autologous PRP + demineralized freeze dried bone graft (DFDBA) with OFD or OFD alone. Clinical parameters recorded were gingival index, plaque index, probing depth (PD), clinical attachment level (CAL), and gingival recession (REC). Radiographic parameters included defect depth reduction, defect resolution, and crestal bone level. All the parameters were recorded at baseline and 12 months postoperatively. Results: Mean PD reduction and CAL gain were greater in PRP + DFDBA (4.88 ± 1.12 mm and 4.26 ± 1.85 mm) and PRP (4.86 ± 2.12 mm and 4.10 ± 1.47 mm) groups than the control group (2.69 ± 1.37 mm and 1.27 ± 0.89 mm). Conclusions: Within the limits of the study, all the three groups showed significant improvement in clinical parameters from baseline to postoperative 12 months. The amount of defect depth reduction and defect resolution treated with PRP alone group were significantly < PRP + DFDBA. The results pertaining to these parameters were significantly better than the control group.